Prosthetic management of an extensive maxillary alveolar defect with an implant-supported restoration. - Fariborz Saadat; Ramin Mosharraf (Tehran University of Medical Sciences, 2013)
Despite the recent developments in peri-implant surgical regenerative procedures, re-establishing the hard and soft tissue contour is still a challenge in cases with severe ridge deficiency. It becomes more difficult when incorrectly placed implants cause screw connections to come out onto the labial surfaces of the teeth. A two-part maxillary implant supported fixed restoration was constructed. The first part was consisted of a screw retained sub-structure that replaced gingival portions of the deficient maxilla and the second part was a cement retained super-structure that reconstructed the anatomical crowns of the lost teeth. In this way awkwardly placed implants did not interfere with the desired esthetic result. Another great advantage was that the alterations or repairs on cemented crowns can easily be carried out without compromising the entire construction.